Conservation of heritage as a non-violent resistance against foreign occupation / Ziad M. M. Shehada, Naziaty Mohd Yaacob and Nila Inangda Manyam Keumala - M. Shehada, Ziad M.; Mohd Yaacob, Naziaty; Keumala, Nila Inangda Manyam (Faculty of Architecture, Planning & Surveying and UiTM Press, 2013)
The conservation of old buildings and monuments with heritage value around the world is implemented as an effort to preserve, highlight and honour historical, cultural and religious significance. But it is entirely different in Palestine today. Here, the process of conservation took on a more drastic task of being a tool of resistance against foreign occupation. Building conservation becomes a necessity for much needed economic and social development. This article focuses on politics and space in Hebron (Al Khalil) city, one of the victims of the ongoing Palestine-Israeli conflict. The research methodology adopted followed the adaptive and analytical methods to analyse the urban space creation in old Hebron, a conflict of two entirely different objectives from two opposing political divides; colonializing projects of dismemberment by a foreign power and conservation as well as revitalization attempts of oppressed, rightful citizens. These conservation and revitalization projects target the rehabilitation of the social and urban fabric through spatial analysis of maps between 1994 and 2007. This article will show that illegal Israeli settlements created a splitting built-up geography which successfully isolated people according to ethno-national, gender and social classes. Their main aim is 'urbicide' However, to a certain extent, the rehabilitation projects in 1996 managed to foil this insidious attempt, blocking or redirecting the Israeli occupation sprawl.